(untitled) (Contemporary Education and Teaching Research, 2023)
In this paper, issues related to the reform of the flight professional curriculum are explored in depth against the background of engineering education accreditation. By elaborating on the importance and necessity of flight professional curriculum reform, a series of practical reform initiatives are proposed. The results of the study show that, in the context of engineering education certification, the reform of flight professional curriculum should adopt strategies such as an industry-oriented curriculum, increasing practical activities in teaching links, promoting the integration of multidisciplinary contents, and improving the evaluation mechanism of the curriculum system, to improve the quality of education and cultivate high-quality flight talents.